The Form of Love and Loyalty in the Animated Film â€œBilal: a New Breed of Heroâ€ By Ayman Jamal: The Perspective of Triangular of Love Theory of Robert J. Sternberg - izzah Himayatud Dauliyah; abdul basid (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2021)
Love and loyalty is one part of the package that helped stronger in some of relationship. What is love and loyalty in this research is not about love in the sense of romance between a man and a woman. Love and the loyalty which that will be studied in this research is about between families, friends, society, also between prophet and God. There for this research focuses on forms of love and loyalty beside of film